Telaah Yuridis terhadap Pengaturan Restorative Justice di Kepolisian - Rena Yulia; Aliyth Prakarsa (Wajah Hukum, 2021)
Police institutions are the first and main gate in law enforcement efforts. First, the police institution in charge of carrying out each criminal case’s enforcement, then the next stage will be determined by the police. The practice of law enforcement so far tends to be retributive justice, so that only a few cases can be resolved in the police investigation process. Restorative justice appears by offering various advantages, including a simple settlement process, involving both parties, both perpetrators and victims, and the role of a third party to mediate, so that cases can be resolved according to the agreement. The police, as the first institution in the law enforcement process, had already issued regulations regarding the application of restorative justice, as a form of law enforcement efforts to change retributive law enforcement. The purpose of this research judicially examined the regulation of restorative justice at the police investigation phase in line with the enactment of the regulation of the Chief of Police Number: SE/8/VII/2018 concerning the Application of Restorative Justice in the Settlement of Criminal Cases and the Regulation of the Chief of the Indonesian Police Number 6 of 2019 concerning Criminal Investigation. This research used a qualitative research method with the type of normative legal research through a statutory approach